WhatsApp Chat Visualizer: A Visualization of WhatsApp Messenger’s Artifact Using the Timeline Method - Hardiansyah Shidek; Niken Cahyani; Aulia Arif Wardana (International Journal on Information and Communication Technology (IJoICT), 2020)
WhatsApp is a medium that everyone can use to interact and to share information effectively and efficiently. However, it can be misused for criminal activities. Analyzing WhatsApp' artifacts is quite challenging as the suspect may have a lot of random conversational data to be considered. This makes it difficult for the trial process to obtain digital traces that can be identified in malicious activities such as knowing who was involved when the conversation was held and the timespan. Therefore, in this research, a social media investigation of WhatsApp was carried out by acquiring data from rooted Android devices that were used as target devices for forensic activities. A python-based application is developed to show the content of the conversation, and a web-based application is presented to visualize the data using the Timeline method. Experimental results in this research display important timeline information such as information about who was involved when and what time the conversation was carried out with the suspect.